Biochemical Characterization of Two Acid Phosphatases Purified from Breadfruit (Artocarpus communis) Seeds - Hubert Kouassi Konan (Science Faculty of Chiang Mai University, 2019)
In present study, purification and characterization of two acid phosphatases (EC 3.1.3.2) from breadfruit seeds (Artocarpus communis) were conducted. The purification procedure consisted of ion-exchanges, size exclusion and hydrophobic interaction chromatography. The enzymes designated AP1 and AP2 had native molecular weights of approximately 61.05 ± 2.2 and 24.9 ± 1.7 kDa, respectively, and there functioned as monomeric structures. The two isoforms isolated exhibited pH and temperature optima at 5.6 and 55 °C, respectively. The purified enzymes were stable at 37 °C and their pH stability was in the range of 5.0-6.0. They required no metal ion as a co-factor. Zn2+, DTNB and SDS inhibited the acid phosphatases activity. Substrate specificity revealed that the two acid phosphatases hydrolyzed a broad range of phosphorylated substrates mainly consisting of natural substrates such as adenosine-5’-triphosphate (ATP) and sodium pyrophosphate. Moreover, the purified enzymes exhibited a significant phytase activity. These findings suggest that the two acid phosphatases might play a key role in metabolic processes and in reducing the amount of phytate, an antinutritional substance contained in this plant seed. Consequently, the purified enzymes can find potential applications in food industries.